PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING PADA MATERI GERAK HARMONIK SEDERHANA TERHADAP KETERAMPILAN PROSES SAINS KELAS X SMA NEGERI 1 TUALANG - Br Hombing, Rosiana; ', Yennita; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of learning inquiry trainingmodel on simple harmonic motion lessons to the students' science process skills ingrade X SMA Negeri 1 Tualang. The type of this study was quasi experiment with IntactGroup Comparison design and involved 1 control class and 1 experimental classconsisting of 68 students. The instrument used in this research is a science skill testconsisting of 18 validated description questions. The result of the analysis shows thatthe six aspects of science process skill consist of observation skills, collecting andprocessing the data, planning the experiment / research, formulating and testing thehypothesis, formulating the explanation and drawing conclusions in the experimentalclass with the treatment using inquiry training model higher than the control classUsing conventional models. Based on the data analysis and discussion it can beconcluded that the inquiry training model positively influences the science process skillson simple harmonic motion lessons.Keywords: Inquiry training model, Process Science Skill, Simple Harmonic Motion